Isolation and Identification of Secondary Metabolic Compounds from Mangrove (Rhizophora mucronata) and their Bioactivity Against Escherichia coli and Staphylococcus aureus Bacteria - Ligina, Anisa Sandhya; Sudarmin, Sudarmin (Indonesian Journal of Chemical Science, 2022)
Bacteria are often found as the cause of disease in the human body because they are pathogenic. One of the bacteria that cause infectious diseases is Escherichia coli and Staphylococcus aureus. Mangrove plants that are rich in secondary metabolites are used to obtain antibacterial substances that can play a role in inhibiting bacterial growth. The purpose of this study was to determine the presence of secondary metabolites of alkaloids in mangrove plants (Rhizophora mucronata) and to determine the antibacterial activity of alkaloid compounds in inhibiting the growth of Staphylococcus aureus and Escherichia coli bacteria. The research method was carried out by remaceration and isolation of alkaloid compounds, analysis of thin-layer chromatography (TLC) and column chromatography, and characterization tests using FT-IR and UV-Vis. The results of the analysis showed the presence of isoquinoline-derived alkaloids supported by FT-IR absorption at 3317 cm-1 indicating the N-H functional group which is a characteristic of alkaloids and the UV-Vis wavelength of 230 nm. These compounds can inhibit the growth of Staphylococcus aureus bacteria by 2 nm and Escherichia coli by 0 nm. The inhibition obtained against Escherichia coli bacteria was caused by the cell membrane layer of gram-negative bacteria consisting of 3 layers so that it was resistant to antibacterial and difficult to penetrate. Staphylococcus aureus only has a single layer, so it is more easily penetrated by antibacterials by causing lysis and inhibiting DNA intercalation.